PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA MELALUI MOTIVASI KERJA PADA PT. PETROIL INDONESIA - Asrun Tonga; Nurul Huda (Universitas YARSI, 2019)
This study aims to analyze the factors that affect the performance of PT. Petroil Indonesia. The research focus used is the compensation variable and work environmentvariable on performance through work motivation. In order to know how far the influence of variables of compensation and work environment variables affect the performance factorsthrough employee motivation, the researcher in this case has done the research with the sampling model used in this research is non probability sampling with slovin method sothat the obtained sample as much as 248 of respondents from 650 respondents. Instrument calibration is done to test the validity of grain and reliability coefficient. Grain validity wascalculated by using correlation product moment coefficients and reliability was calculated using the coefficient of cronbach's alpha.The hypothesis used in this research is usingStructural Equation Modeling (SEM) analysis technique. From the results of the study showed all hypothesis proposed in this research accepted. This means that there is a significant influence between compensation, work environment to work motivation and performance.